2016
DOI: 10.1128/jvi.01532-15
|View full text |Cite
|
Sign up to set email alerts
|

Sabin Vaccine Reversion in the Field: a Comprehensive Analysis of Sabin-Like Poliovirus Isolates in Nigeria

Abstract: To assess the dynamics of genetic reversion of live poliovirus vaccine in humans, we studied molecular evolution in Sabin-like poliovirus isolates from Nigerian acute flaccid paralysis cases obtained from routine surveillance. We employed a novel modeling approach to infer substitution and recombination rates from whole-genome sequences and information about poliovirus infection dynamics and the individual vaccination history. We confirmed observations from a recent vaccine trial that VP1 substitution rates ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 63 publications
4
75
0
Order By: Relevance
“…First, three substitution events occurred almost invariantly in all lineages deriving from OPV2. These substitutions include the known A481G and U2909C attenuation reversions, as well as an additional reversion at U398C in the 5’ UTR (Famulare et al, 2015; Macadam et al, 1991; Muzychenko et al, 1991). In all lineages with enough resolution (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, three substitution events occurred almost invariantly in all lineages deriving from OPV2. These substitutions include the known A481G and U2909C attenuation reversions, as well as an additional reversion at U398C in the 5’ UTR (Famulare et al, 2015; Macadam et al, 1991; Muzychenko et al, 1991). In all lineages with enough resolution (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…To date, limited analyses of localized cVDPVs (Burns et al, 2013; Endegue-Zanga et al, 2015; Famulare et al, 2015; Hovi et al, 2013; Tao et al, 2013) have been undertaken, and many aspects of the evolutionary and epidemiological dynamics of cVDPVs remain unclear (Duintjer Tebbens et al, 2013). Understanding the evolutionary path(s) that leads from the attenuated and non-hazardous form of the virus into a circulating and pathogenic virus is central to the global poliovirus eradication efforts, for prediction of future epidemics, to understand the risks of current strategies and for designing new and safer vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…Nucleotide A 481 contributes to the attenuation phenotype of this vaccine virus, but it readily reverted to G in organisms of vaccinees, which is the event expected to disrupt the tertiary interaction. However, the potential for formation a stable C 398 -G 481 pair was regained in most isolates due to the reversion at position 398 as well (234,311,322) (Fig. 4B).…”
Section: Rehabilitation After Adverse Changes In the Untranslated Regmentioning
confidence: 99%
“…As noted above, the Sabin strain of this serotype has a destabilizing mutation at position 480 (A to G) contributing to its attenuated phenotype, but this destabilization is not usually conserved in vaccinees and their contacts. The strengthening of this base pairing might be accomplished not only by the reversion (G 480 A) but also by a compensating pseudoreversion (U 525 C) (311,322), which also resulted in a similar increase in virulence (323) and in restoration of the in vitro translation efficiency (311). Structural modeling suggested that G 481 of the predecessor of the Sabin-2 strain, strain P712, could potentially participate in a long-range interaction with C 398 , supporting the generation of a tertiary structure element (311) (Fig.…”
Section: Rehabilitation After Adverse Changes In the Untranslated Regmentioning
confidence: 99%
“…on Earth wild poliovirus and the emergent vaccine-derived polioviruses (cVDPVs) continues to cause concern over the resurgence of poliomyelitis (52)(53)(54)(55) . A synthetic poliovirus was assembled in 2002 (56) , codon deoptimized in 2006 (57,58) , codon pair deoptimized in 2008 (59) , and dinucleotide deoptimized in 2009 (11) .…”
Section: Development Of a Robust Live-attenuated Poliovirus Vaccine mentioning
confidence: 99%